Allium ursinum L. (Amaryllidaceae) – новий вид для флори НПП “Пирятинський” - Kovalenko, Oleksii; Kalista, Mariia (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2022)
In Ukraine, Allium ursinum is a rare species of the state level of conservation, isolated locations of which occur very rarely on the territory of the left bank of the river Dnipro. A new location discovered on the territory of National Nature Park “Pyriatynskyi” is isolated and confined to the floodplain gallery forest of the association Alnion incanae Pawłowski et al. 1928. On the territory of the Nature Park “Pyriatynskyi”, the species is represented by a small, incomplete population with a left-sided spectrum. Considering the chorology of the species in the region and the demographic characteristics of the population, this new locality was most likely formed as a result of the recent accidental introduction of the species from the northern enclaves of the Chernihiv oblast or purposeful planting of plants by the local citizens. Taking into account the proximity of A. ursinum growing locality to popular recreation areas, it is necessary to introduce monitoring research of the state and structure of the population and develop special protection measures to conserve this species on the territory of National Nature Park “Pyriatynskyi”.